PERSEPSI KEPALA SEKOLAH TERHADAP PEMBELAJARAN PJOK TINGKAT MTS/SMP SE KECAMATAN KAMPAR - Fikri, Ikhsan; Ramadi, Ramadi; Rahmatullah, M. Imam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim of this research is to determine the perceptions of schoolprincipals regarding PJOK learning at the MTS/SMP level in Kampar District. Thisresearch is quantitative descriptive research which provides an overview of the objectbeing studied. This research was conducted by researchers at MTS/SMP in KamparDistrict, 27 May - 31 May 2024. The researcher used two questionnaire tables, namelythe table with the Facilities and Infrastructure indicator containing 12 statements thatthe researcher had made and the table with the PJOK learning process indicator whichcontained 21 statements that have been made by researchers. Based on the researchresults, the conclusion obtained in this research is: School Principals' Perceptions ofPJOK Learning at the MTS/SMP Level in Kampar District are included in the valuerange of 81%-100% or in the very strong category with a percentage of 82%.Key Words: Principal's Perception, PJOK Learning, Middle School Leve